S SISTEM PENENTUAN UPAH PADA MANAJEMEN HOME INDUSTRY BAWANG MERAH DI TINGGAR BANDAR KEDUNGMULYO JOMBANG PERSPEKTIF ETIKA BISNIS SYARI’AH: WAGE DETERMINATION SYSTEM IN THE MANAGEMENT OF THE RED ONION HOME INDUSTRY IN TINGGAR BANDAR KEDUNGMULYO JOMBANG SHARI'AH BUSINESS ETHICS PERSPECTIVE - Eka Erniah; Islami, Trinah Asi (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2024)
This research aims to determine and analyze the wage management system in the red onion home industry in Tinggar Bandar Kedungmulyo Jombang, analyzing wage eligibility standards according to the Employment Law in providing wages in accordance with sharia business ethics. This research uses primary data sources and secondary data sources. Data were collected using interviews and questionnaires which were then analyzed using descriptive inductive methods. With the aim of knowing business behavior in managing the home industry in wage standards based on Employment Law Number 13 of 2003 Article 77 Paragraph (1) working time and Article 88 Paragraph (1) and Paragraph (2) wage standards in the practice of providing appropriate wages with sharia business ethics